Development and Current Status of Suspended Monorail Vehicle - LI Fu; XU Wen-chao; AN Qi (机车电传动)
Development history of suspended monorail vehicle was introduced briefed, and the current status of suspended monorail vehicles classified by bogies style was introduced. Furthermore, the technical characteristics of suspended monorail vehicle were described and compared to straddle type monorail for analyzing the merits and demerits. At last, application prospect of suspended monorail in China was also given.